Effect of process parameters on micro-textured surface generation in feed direction vibration assisted milling. (1st February 2020) - Shen, X.H.; Shi, Y.L.; Zhang, J.H.; Zhang, Q.J.; Tao, G.C.; Bai, L.J.
Highlights: 2D Kinematic analysis, 3D simulation coupled with experimental investigation by a self-made setup was performed to explore the effect of the milling parameters and vibrating parameters on the generation of micro-textured surface in feed direction ultrasonic vibration assisted end milling process. Two key parameters, i.e. η and λ, was defined and supposed to be significant to the actual tool track and empty cutting time and finally the surface finishing. Three typical surface texture, which are "micro-rib", "micro-scale" and "micro-wave", were simulated and experimentally fabricated at low spindle speed, medium spindle speed and high spindle speed, respectively. The predictive surface textures are in consistent with those of experiment. At a certain spindle speed (a certain spindle speed means a certain η), λ influences the size of overlapped area of multiple cutting and thus produce an effect on the size of fabricated micro-structure. The surface topographies and roughnesses of the obtained three kinds of micro-textured surfaces, together with their tribological behaviors under strave oil lubrication condition, were investigated. As results, the fabricated micro-textures cause the deterioration of surface roughness in most experimental cases owing to the peak-valley micro structure resulting from excited vibration. However, the micro-textures studied in this case all make a great contribution to the improvement of surface friction property, particularly in term of load bearing capacity due to the lubricant absorption and reservation function of micro-texture. Too low spindle speed may lead to much increase in surface roughness, which then affect the surface tribological performance adversely, and medium spindle speed is preferable to achieve micro-textured surface with better load bearing capacity. Abstract: Surface with certain macro/micro/nano structure has been earning more and more attentions owing to its good tribological behavior. However, some complex texture pattern is hard to fabricate, which hinders its wide application. In this study, feed direction ultrasonic vibration assisted milling (FDUAM), was proposed to realize the easy fabrication of micro-textured surface. Based on tool mapping principle, kinematic analysis was carried out aiming to explore the effect of main process parameters on tool trajectory, and also a surface topography simulation model was build. The numerical analysis results were validated by comparing results with experimental data. Three surface texture patterns, which are "micro-rib", "micro-scale" and "micro-wave", were realized at low spindle speed, medium spindle speed and high spindle speed, respectively. A preliminary friction test was at last conducted to investigate the tribological behaviors of various micro-textured surfaces. As results, it is found that the final surface topography is greatly influenced by the matching of vibrating parameters and milling parameters, two key parameters, i.e. η and λ, was supposed to be significant to the actual tool path and empty cutting time and finally the surface finishing. Friction test shows that although the fabricated micro-textures lead to the deterioration of surface roughness in most experimental cases, the three fabricated micro-textures studied in this case all make a great contribution to the improvement of surface friction property, particularly in term of load bearing capacity.